АСТАРЛЫ СӨЗДЕРДІҢ ДАМУ ЖОЛЫ. - Қатбаева, Г. Қ. (Journal of Oriental Studies, 2016)
В статье описывается история развития особенноговида фразеологизмов – иносказании в китайском языке.In given article the history of development of anespecial kind of phraseological units – an allegory isdescribed on Chinese language